IMPLEMENTASI ALGORITMA DIJKSTRA UNTUK MENENTUKAN JALUR TERPENDEK DALAM DISTRIBUSI BARANG - Ikhsan Baharudin; Ahmad Jaka Purwanto; Teguh Rahayu Budiman; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2021)
PT. X is a company domiciled in Gedebage, Bandung which is engaged in the manufacturing industry by producing precision parts using CNC machines. PT. X is a sub-contracting company that usually serves project work from other companies. PT. Y and PT. Z is a regular customer who often works with PT. X. So that PT. X often sends finished products directly to PT. Y who is domiciled on Jl. Gatot Subroto, Bandung and also PT. Z who is domiciled on Jl. Pajajaran, Bandung. To minimize the cost of distribution of goods, PT. X must determine an adequate path taking into account the optimization of transportation costs. One of the variables that affect transportation costs is distance. It is assumed that the optimal path for transportation costs is the shortest distance using the Dijkstra method. This test uses data from Google Maps to find out the distance to each destination, making it easier to get the shortest path. Obtained the shortest path from PT. X to PT.Y is 12.3 Km via West Java Police then Carefour, while the shortest route is from PT. Y to PT. Z is 10.7 Km via Simpang Lima then Vie Hotel Westhoff. So that the optimal total mileage for distributing goods is 23 Km.